Identification of Puccinia striiformis races from the spring wheat crop in Xinjiang, China - Ma, Jinbiao; Awais, Muhammad; Chen, Li; Yang, Hong; Lai, Hanlin; Shen, Yuyang; Wang, Huiqing; Li, Guangkuo; Gao, Haifeng (Frontiers in Plant Science, 2023)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is a foliar disease that affects both winter and spring wheat crops in Xinjiang, China, which links with Central Asia. Race identification of Pst from spring wheat in Xinjiang was not done before. In this study, a total of 216 isolates were recovered from stripe rust samples of spring wheat in the region in 2021 and multiplied using the susceptible cultivar Mingxian 169. These isolates were tested on the Chinese set of 19 wheat differential lines for identifying Pst races. A total of 46 races were identified. Races Suwon-11-1, Suwon11-12, and CYR32 had high frequencies in the spring wheat region. The frequencies of virulence factors on differentials 'Fulhard' and 'Early Premium' were high (> 95%), whereas the virulence factor to differential 'Triticum spelta var. Album' (Yr5) was not detected, while virulence to other differentials showed variable frequency within different counties. The predominant races in winter wheat in the same season were also detected from spring wheat cultivars, indicating Pst spreading from winter wheat to spring wheat crops. Deploying resistance genes in spring and winter wheat cultivars is critical for control stripe rust.